Pertanggungjawaban Pidana Korporasi atas Pencemaran Radioaktif Cesium-137 - Munjiyah, Amrina; Rismana, Daud; Ayunisa, Qurota; Nurul Huda, Muhammad; Nurkholisah, Siti; Nugroho, Afrizal Eko (Institut Agama Islam Negeri Kendari, 2025)
The case of indications of caesium-137 radioactive contamination in the Cikande modern industrial area, Banten, is used in this study as a normative illustration to describe the potential for serious threats to health and the environment and to indicate a legal vacuum. This study aims to analyze the possible forms of corporate liability outside the official nuclear industry if it is proven to have caused contamination, with reference to the provisions of Law Number 32 of 2009 concerning Environmental Protection and Management (PPLH Law) and Law Number 10 of 1997 concerning Nuclear Energy. The research method used is normative juridical with a conceptual approach, using cases as normative illustrations to demonstrate the urgency of the need for legal reform. The results of the analysis show that the environmental legal framework provides a normative basis for applying liability to corporations outside official nuclear installations that are proven to be the cause of contamination by using the principle of strict liability. This study recommends reformulating the Nuclear Energy Law by expanding the scope of legal subjects to include activities outside official nuclear installations that have the potential to cause radiation hazards and creating more comprehensive laws and regulations to prevent and deal with the threat of radioactive contamination to the environment